2015
DOI: 10.1039/c5cp02047f
|View full text |Cite
|
Sign up to set email alerts
|

Gramicidin A disassembles large conductive clusters of its lysine-substituted derivatives in lipid membranes

Abstract: N-terminally substituted lysine derivatives of gramicidin A (gA), [Lys1]gA and [Lys3]gA, but not glutamate- or aspartate-substituted peptides have been previously shown to cause the leakage of carboxyfluorescein from liposomes. Here, the leakage induction was also observed for [Arg1]gA and [Arg3]gA, while [His1]gA and [His3]gA were inactive at neutral pH. The Lys3-containing analogue with all tryptophans replaced by isoleucines did not induce liposome leakage, similar to gA. This suggests that the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…At a high local concentration, the CF emission is self-quenched. 36 This allows its release in solution to be monitored by following the fluorescence enhancement as a function of time both in the absence and in the presence of an increasing peptide concentration. The kinetic curves and the leakage percentage at 1500 s are reported in Fig.…”
Section: Ll-iii Effects On Membrane Permeabilitymentioning
confidence: 99%
“…At a high local concentration, the CF emission is self-quenched. 36 This allows its release in solution to be monitored by following the fluorescence enhancement as a function of time both in the absence and in the presence of an increasing peptide concentration. The kinetic curves and the leakage percentage at 1500 s are reported in Fig.…”
Section: Ll-iii Effects On Membrane Permeabilitymentioning
confidence: 99%
“…Computer simulations have shown that this method can theoretically improve the reconstruction of membrane proteins. We applied it to study the clustering of gramicidin in liposomes [83]; however, the method did not allow achieving high resolution.…”
Section: Revolution In Structural Biology -Cryo-em Structures Of Ion Channels With Nearatomic Resolutionmentioning
confidence: 99%
“…There are several physical models that were proposed for the membrane disruptive activity of AMPs. The barrel stave model involves the insertion of the peptide into the membrane in forming a purely proteinaceous pore [22], the toroidal pore model causes bending of the lipid membrane leading to the formation protein and lipid headgroup lined pore [23], and the carpet model which causes destabilization of the cell membrane through a mass action effect similar micellization type mechanism [24].…”
Section: Introductionmentioning
confidence: 99%